Investigating the Impact of the Hospital Information System on the Performance of Management Units at Pasteur Hospital in Bam from the Perspective of Managers - Mohammad Javad Akbarian Bafghi; Shaghayegh Shafa; saeideh Baghdervazeh; Sajjad khosravi; Rasheed Pourhamidi (Rāhburdhā-yi Mudīriyyat dar Niẓām-i Salāmat)
Background: The Hospital Information System (HIS) is a comprehensive information management system in hospitals that plays a significant role in the quality of managers' decisions. Therefore, this study aimed to examine the impact of the HIS on the performance of management units at Pasteur Hospital in Bam from the managers' perspective in the year 2023. Method: The present study was an applied, descriptive, and cross-sectional study conducted in  2023. The performance of management units was examined in three clinical, human resources, and financial indicators. The study population consisted of all the managers at Pasteur hospital in Bam at three levels: executive, middle, and top management, who were entered into the study through a census (38 individuals). Information was collected using a standardized questionnaire, and for data analysis, SPSS 27 software and appropriate descriptive and analytical statistical tests (independent t-test and ANOVA) were used. Results: Participating managers were 76.30 % women and 23.70 % men. 73.70 % of them had a bachelor's degree and most of them were in the category of operational and middle managers. From the point of view of the managers of the HIS, the greatest impact on the indicators of the trend of treatment activities (28.60 ± 5.35), cost (50.00 ± 3.60), productivity and training (32.35 ± 12.81) and the least impact on the indicators of information exchange (25.50 ± 4.67), income (32.33 ± 0.57), salary and wages (10.50 ± 5.00). In this study, three components—clinical, financial, and human resources—were examined separately by gender, education level, and management levels. The results of the independent t-test indicated that there was a significant difference only in the clinical component based on gender (p = 0.04) Conclusion: To enhance the effectiveness of the HIS on managers' performance, it is essential to first conduct a comprehensive needs assessment of all management units. This needs assessment should identify the essential tasks and specific needs of each unit, and based on that, the enhancement of the HIS should be aligned with these needs. Moreover, paying special attention to the dimensions and indicators that receive less impact from this system can help improve the overall performance of the system and enhance its effectiveness in all aspects.